Could plasma zinc be a predictor for mortality and severity in sepsis syndrome? - Visalakshy, Jyothi; Visalakshy, Jyothi; Surendran, Sandeep; Pillai, Madhavan Pillai Gopalakrishna; Pillai, Madhavan Pillai Gopalakrishna; Rajendran, Aiswarya; Rajendran, Aiswarya; Sherif, Akil Adrian; Sherif, Akil Adrian (International Journal of Research in Medical Sciences, 2017)
Background: While many factors are known to play a role in outcomes of sepsis, the role of micronutrients such as zinc remains a gray area. This study assesses the correlation of plasma zinc levels with mortality and severity of sepsis. Objective was to study the association between plasma zinc levels with mortality and severity of sepsis. Methods: Comparative prospective observational study which included 89 patients with proven sepsis according to the society of critical care medicine (SCCM) guidelines. The study was conducted at a tertiary care centre in South India. A total of 89 patients who were admitted into the medical ICU directly from ER, from December 2014 to August 2015 were chosen for the study after satisfying specific inclusion criteria and divided into 2 outcome groups based on mortality. Results: There was a significant association between plasma zinc (categorized as low, normal and high plasma zinc) and outcome. While the severity of sepsis as per SOFA score on admission did not have an association, there was a significant association between plasma zinc and the 48-hour SOFA score. Conclusions: Higher plasma zinc values had lower mortality and lower 48 hours SOFA score, strengthening the hypothesis regarding the role of zinc in the immune response to sepsis. More research is needed regarding the role of zinc in assessing the severity and predicting the mortality of patients with sepsis.